Super-héros et science-fiction française dans l’immédiat après-guerre - Désirée Lorenz (ReS Futurae)
Comics production in France in the immediate post-war period has to deal with a complex situation. The children’s literature is facing a complete reorganization driven by economic and political measures that many publishers will not escape unscathed. American series that had stimulated the creativity of cartoonist and publishers before the war, such as those of science fiction telling space and / or exotic adventures of superhumans-like with more or less fantastic powers and / or extraordinary technological tools are strongly criticized. But, though the hunt for translations of foreign comics was open, and their presence would become rarer throughout the 40s and 50s, this literature has strongly influenced the graphic style and narrative imagination of French cartoonists, and thus impregnated the French post-war science fiction. The creation of French superheroes’ comics such as Fulguros (1947), Atomas (1948), or Satanax (1948) is a piece of choice for those interested in French science fiction’s formation in this period. It embodies in a particular way a science fiction model then considered deviant. We propose to draw the portrayal of this emerging French science fiction comics, which is necessarily unstable, moving and whose graphic, narrative and ideological characteristics are often shelved.